2022
DOI: 10.1097/01.ogx.0000822436.67205.20
|View full text |Cite
|
Sign up to set email alerts
|

Live Birth With or Without Preimplantation Genetic Testing for Aneuploidy

Abstract: signaling pathways closely related to oocyte aging, including the meiosis signaling pathways containing CDC26. q-PCR confirmed the RNAsequencing results, including decreased CDC26 mRNA and protein level in oocytes from older compared with younger women. Recombinant overexpression of CDC26 rescued meiotic defects. After 2 days in culture, 37.5% of the germinal vesicle stage oocytes injected with the CDC26 construct developed to metaphase, versus only 16.7% of controls. These results demonstrate that CDC26, a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…5,[7][8][9][10] A few studies have suggested that IVF with preimplantation genetic testing for aneuploidy results in higher implantation rates 3,11 and lower miscarriage rates 3,4 than IVF alone. However, the effectiveness of preimplantation genetic testing for aneuploidy and generalizability of these studies is debated, 2,8,[12][13][14][15] because the majority of randomized controlled trials of preimplantation genetic testing for aneuploidy have failed to demonstrate improved outcomes. 15,16 Of growing concern is a high false-positive rate for aneuploidy with preimplantation genetic testing for aneuploidy that may result in the discard of potentially viable embryos 17 and reduced chance of pregnancy for women without resources to undergo additional IVF cycles.…”
Section: Discussionmentioning
confidence: 99%
“…5,[7][8][9][10] A few studies have suggested that IVF with preimplantation genetic testing for aneuploidy results in higher implantation rates 3,11 and lower miscarriage rates 3,4 than IVF alone. However, the effectiveness of preimplantation genetic testing for aneuploidy and generalizability of these studies is debated, 2,8,[12][13][14][15] because the majority of randomized controlled trials of preimplantation genetic testing for aneuploidy have failed to demonstrate improved outcomes. 15,16 Of growing concern is a high false-positive rate for aneuploidy with preimplantation genetic testing for aneuploidy that may result in the discard of potentially viable embryos 17 and reduced chance of pregnancy for women without resources to undergo additional IVF cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, subgroup analysis based on maternal age extracted from a larger, randomized study was the focus of much discussion. However, despite the recent enthusiasm, since the debate, another randomized controlled study again showed no benefit to PGT‐A to improve IVF improvements 48 . However, other studies including a retrospective study from the United Kingdom, continue to support increase in livebirths with PGT‐A and challenge local guidelines advocating restriction 47 …”
Section: Discussionmentioning
confidence: 99%
“…Futile transfers of aneuploid embryos are, unfortunately, an implicit outcome of any suggested consecutive transfer of untested embryo protocols-an aspect that is ignored in some reports. 28 We propose that any negative effect of biopsy within any clinic would be better assessed by defined, specific studies and have suggested how such an evaluation might be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The implantation rates reported by Yan et al, 28 being equal to euploid embryos identified after biopsy and PGT-A, either suggest a very high efficacy of the clinic selection of euploid embryos, approaching a maximum value, and/or alternatively, demonstrates a negative impact of the biopsy process. However, it does not demonstrate an equivalence of the two.…”
Section: Affect On Rctsmentioning
confidence: 94%
See 1 more Smart Citation